Biomechanical analysis of the late approach and the take off in the indoor women`s long jump - Panoutsakopoulos, V.; Theodorou, A.; Fragkoulis, E.; Kotzamanidou, M. C. (Journal of Human Sport & Exercise, 2021)
Aim of the study was to provide evidence concerning the biomechanical parameters of contemporary Women`s long jump in indoor competition. The final six steps and the take-off of 11 jumps (6.88 ± 0.23 m) were recorded (panning camera; sampling frequency: 300 fps) in an indoor competition. The examined parameters were a) the step parameters, the percentage distribution of adjustment (ADJ%) and the inter-limb symmetry angle (Theta SYM) in the late approach, b) the joint angles and the take-off parameters. Pearson`s correlation analysis revealed that approach velocity (9.8 ± 0.3 m/s) was significantly correlated (r = .86, p = .001) with effective distance (6.96 ± 0.23 m). The largest ADJ% (57.6 %) was executed at the penultimate step which was 12.2 ± 2.8 % larger than the last step. An inter-limb difference was revealed for step frequency (t10 = 6.965, p < .001) due to the large asymmetry observed (Theta SYM = 5.54 deg). The knee angle of the push-off leg at take-off was 171.2 ± 4.7deg. Resultant velocity (8.3 ± 0.4 m/s), height (1.15 ± 0.05 m) and angle (20.7 ± 2.3 deg) of take-off significantly predicted effective distance (F3,7 = 12.671, p = .003, R2 = .844). The present findings are in reasonable agreement with previous research. Future studies should examine the possible reliance and asymmetry for the step parameters in the final approach.